Intubation in propofol-treated status epilepticus: a cohort study - Maya Mikutra-Cencora; Jeanne Teitelbaum (Frontiers in Medicine)
IntroductionThe management of status epilepticus (SE) often includes endotracheal intubation with mechanical ventilation to address respiratory depression, especially in patients treated with third-line anesthetic agents such as propofol. At our center we use sub-anesthetic propofol as a first line anti-epileptic for SE without intubation. We aimed to assess the performance of our treatment algorithm and to determine whether intubation in these patients improves outcomes.MethodsAll adult patients with SE treated with propofol at a tertiary neuro-intensive care unit from 2015 to 2022 were identified through medical records. Survival without new neurological deficits at discharge was the primary outcome; secondary outcomes were the development of common complications. Descriptive statistics were used to assess general outcomes, and multi-variable logistic regressions were performed to compare outcomes between patients who were intubated while on propofol and those who were not, as well as to compare outcomes according to number of days kept intubated after cessation of propofol.ResultsWe identified 162 SE patients treated with low-dose propofol, of which 44 (17%) were not intubated and 118 (83%) were. Our cohort’s survival rate was 85%, and survival without new deficits was 42%. Intubation was not associated with improved survival without new neurological deficits (OR = 1.34, 95% CI 0.372–4.831, p = 0.655) or reduction in complications. Additionally, in patients intubated for management of SE, the number of days kept intubated following cessation of propofol was associated with a decrease in survival without new neurological deficits (OR = 0.016, 95% CI 0.000–0.854, p = 0.042).ConclusionThis study offers encouraging evidence that early sub-anesthetic propofol is a safe and efficient alternative to existing treatment approaches in selected patients. These patients do not require intubation: intubation fails to significantly improve outcomes, and prolonging intubation past cessation of propofol worsens outcomes. These data raise doubts as to the benefits of endotracheal intubation in SE and stress the need to limit the duration of this invasive measure.